Hauntings of Longing: A Mad Autoethnographic Poetic Transcription - Jersey Cosantino (Disability Studies Quarterly, 2021)
This poetry collection explores my grapplings with my Mad and trans identities within the curative, diagnostic, medical model discourses of the medical industrial complex. Using an autoethnographic Mad and trans poesis, I seek to situate these grapplings within historical and present-day systems of power, privilege, and oppression, confronting the hauntings (Gordon, 2008) that arise from my simultaneous complicity in and disruption of these institutionalized structures of harm and violence that disproportionately target bodyminds that are deemed non-normative. By engaging in this process through poetic expression, I center an embodied form of knowledge production that challenges sanist notions of rationality and hetero- and cis-normativity constructed and perpetuated by white settler colonial ideologies. My unearthing of these hauntings (Gordon, 2008) and my relationship to them on an internal, interpersonal, and systemic level is merely a beginning in a life-long journey of trans and Mad becoming.
Keywords: trans; Mad; haunting; autoethnography; diagnosis; cure; medical industrial complex